2021
DOI: 10.30651/jqm.v5i2.7378
|View full text |Cite
|
Sign up to set email alerts
|

Development of augmented reality-assisted health education posters on Covid-19

Abstract: The changes in the social order of life in the new normal era due to the Covid-19 pandemic have caused various sectors of the work environment to create new habitual adaptation policies so that the service process continues to run well. One method used was to use poster media to be displayed in the office environment as a media for health protocol information. The purpose of this research was to create a poster based on augmented reality videos that were suitable for use as media for information on health prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
(13 reference statements)
0
0
0
2
Order By: Relevance
“…Dampak dari kebijakan ini telah menyebabkan hilangnya pekerjaan, penutupan bisnis, penghentian aktivitas ekonomi, pariwisata, maupun pendidikan. Perubahan tatanan kehidupan sosial di era normal baru menyebabkan ragam sektor membuat dan menjalankan kebijakan adaptasi kebiasaan baru dalam lingkungan kerja agar proses pelayanan tetap terus berjalan dengan baik (Saputra & Fajriani, 2021). Hal ini menjadi tantangan tersendiri bagi semua sektor, termasuk sektor pendidikan.…”
Section: Pendahuluanunclassified
“…Dampak dari kebijakan ini telah menyebabkan hilangnya pekerjaan, penutupan bisnis, penghentian aktivitas ekonomi, pariwisata, maupun pendidikan. Perubahan tatanan kehidupan sosial di era normal baru menyebabkan ragam sektor membuat dan menjalankan kebijakan adaptasi kebiasaan baru dalam lingkungan kerja agar proses pelayanan tetap terus berjalan dengan baik (Saputra & Fajriani, 2021). Hal ini menjadi tantangan tersendiri bagi semua sektor, termasuk sektor pendidikan.…”
Section: Pendahuluanunclassified
“…Pada era pasca pandemi, banyak aspek dalam bidang pendidikan dipaksa harus terus menerus bertansformasi. Perubahan tatanan kehidupan sosial di era normal baru menyebabkan ragam sektor membuat dan menjalankan kebijakan adaptasi kebiasaan baru dalam lingkungan kerja agar proses pelayanan tetap terus berjalan dengan baik (Saputra & Fajriani, 2021). Untuk menanggapi hal tersebut, pemerintah terus menerus memperbarui kebijakannya.…”
Section: Pendahuluanunclassified
“…al., 2017) revealed that the QR-Code has contrasting colors and a high level of augmenting ability. QR-Code will make it easier for users to recognize 3D objects that will appear (Saputra & Fajriani, 2021a). Meanwhile, (Atmaja, 2018) explained that the existence of augmented reality would make it easier for academics to understand the material presented.…”
Section: Development and Implementationmentioning
confidence: 99%